Rechallenge with Amisulpride in a Patient with Schizophrenia following a Manic Episode during Previous Therapy. (16th May 2022) - Hu, Li-Yu; Hong, Chen-Jee; Tsai, Shih-Jen; Shen, Cheng-Che
Abstract : Amisulpride is an atypical antipsychotic. It is also effective in treating depression. The potential antidepressant effect raises the concern that amisulpride can induce mania. However, reports of amisulpride-induced mania have been rare. Here, we present the case of a Taiwanese woman with a 22-year history of schizophrenia. At the age 57 years, she developed manic symptoms while on treatment with amisulpride for six weeks. She was immediately admitted to the psychiatric in-patient unit. The manic symptoms completely subsided within eight days without the administration of any mood stabilizer. Readministration of a single dose of 200 mg amisulpride during hospitalization induced the same manic symptoms, which remitted completely within 24 hours without any mood stabilizer administration.